Topical bioassay of Oberon® on Drosophila melanogaster pupae: delayed effects on ovarian proteins, cuticular hydrocarbons and sexual behaviour. Issue 1 (2nd January 2021) - Bensafi-Gheraibia, Hanene; Kissoum, Nesrine; Hamida, Zahia Cirine; Farine, Jean Pierre; Soltani, Noureddine
ABSTRACT: Spiromesifen (Oberon® 240 SC; concentrated solution; Bayer CropScience, Germany) a pesticide derived from spirocyclic tetronic acids, acts mainly though blocking lipid biosynthesis via acetyl-CoA carboxylase. However, its mode of action requires further analyses. This study aims to evaluate the sublethal effects of spiromesifen on the fruit fly Drosophila melanogaster . The treatment was carried out by topical application on newly moulted pupae using two concentrations (LD10 = 21.45 and LD25 = 39.53 μg a.i./pupa). Our results showed that the developmental duration of larvae and pupae were not significantly affected by treatment. However, spiromesifen caused delayed effects on flies that survived from treated pupae. Spiromesifen was found to decrease significantly both the morphometric measurements and the protein contents of ovaries. The protein pattern of ovaries showed a reduction in the number of protein bands affecting the progeny via vitellogenesis. Finally, compared to controls, spiromesifen decreased significantly the amounts of some cuticular hydrocarbons in treated female and male adults. Consequently, in response to the changes in cuticular hydrocarbons, their sexual behaviour was also affected. Our study brings new insights about the multiple effects and physiological consequences of disturbing lipid metabolism.